Occurrence of the Angiotensin-Converting Enzyme–Inhibiting Tripeptides Val-Pro-Pro and Ile-Pro-Pro in Different Cheese Varieties of Swiss Origin - Bütikofer, U.; Meyer, J.; Sieber, R.; Walther, B.; Wechsler, D. (Journal of dairy science, 2008)
The contents of the 2 antihypertensive peptides Val-Pro-Pro (VPP) and Ile-Pro-Pro (IPP) were determined in 101 samples from 10 different Swiss cheese varieties using HPLC with subsequent triple mass spectrometry. In the category of extra hard and hard cheeses, the Protected Denomination of Origin cheeses Berner Alpkäse and Berner Hobelkäse, L’Etivaz à rebibes, Le Gruyère, Sbrinz, Emmentaler (organic and conventional) and in the category of semihard cheeses, the varieties Tilsiter, Appenzeller 14 fat and full fat, Tête de Moine, and Vacherin fribourgeois were screened in the study. The average concentration of the sum of VPP and IPP in the screened cheese varieties varied to a large extent, and substantial variations were obtained for individual samples within the cheese varieties. The lowest average concentration of the 2 tri-petides was found in L’Etivaz à rebibes (n = 3) at 19.1mg/kg, whereas Appenzeller 14 fat (n = 4) contained the greatest concentration at 182.2mg/kg. In individual samples, the total concentration of VPP and IPP varied between 1.6 and 424.5mg/kg. With the exception of a 10-yr-old cheese, VPP was always present at greater concentrations than IPP. Milk pretreatment, cultures, scalding conditions, and ripening time were identified as the key factors influencing the concentration of these 2 naturally occurring bioactive peptides in cheese. The results of the present study show that various traditional cheese varieties contain, on average, similar concentrations of the 2 antihypertensive peptides to the recently developed fermented milk products with blood pressure–lowering property. This may serve as a basis for the development of a functional cheese with blood pressure–lowering property.